Exploratory Analysis of the Anti-Inflammatory Potential of the Ethyl Acetate-Soluble Fraction of Selaginella doederleinii Hieron in IL-1β-Induced Rat Hepatocytes - Pinanti, Honesty Nurizza; Tanaka, Risa; Saito, Yosuke; Minamisaka, Keita; Takayasu, Kaho; Nishizawa, Mikio; Djati, Muhammad Sasmito (Trends in Sciences, 2026)
Interleukin-1β (IL-1β), a key pro-inflammatory cytokine, promotes inducible nitric oxide synthase (iNOS) expression in hepatocytes, leading to excessive nitric oxide (NO) production and liver inflammation. Selaginella doederleinii Hieron is a medicinal plant traditionally used to treat various diseases, but its anti-inflammatory potential in hepatic inflammation models remains insufficiently explored. This exploratory study evaluated the anti-inflammatory potential of crude fractions of S. doederleinii, with implications for hepatoprotection, using an IL-1β-induced primary rat hepatocyte model and explored potential underlying molecular mechanisms. Fractions A (ethyl acetate), B (n-butanol), and C (aqueous) were assessed for NO inhibition, iNOS expression, and cytotoxicity. Fraction A (ethyl acetate) exhibited the strongest NO inhibitory activity (IC₅₀ = 15.69 µg/mL), showed no cytotoxicity, and qualitatively displayed a trend toward reduced iNOS expression. The representative Western blot analysis of iNOS provided visual support for the NO inhibition observed in the assay. Exploratory transcriptomic profiling suggested altered expression of genes related to the NF-κB and TNF pathways, including Rela and Nos2, thereby providing hypothesis-generating insights. LC–HRMS analysis tentatively annotated several compounds in Fraction A. In silico docking predicted that emodin-8-O-β-D-glucopyranoside showed relatively higher binding potential to IL-1β at site A, suggesting a possible interference with the IL-1β/IL-1R1 interaction. Collectively, these findings provide preliminary and exploratory in vitro and in silico evidence that the ethyl acetate-soluble fraction of S. doederleinii may exert anti-inflammatory activities in IL-1β-induced hepatocytes, warranting further validation. HIGHLIGHTS The ethyl acetate-soluble fraction of Selaginella doederleinii Hieron (Fraction A) showed the strongest inhibition of NO production with no cytotoxicity. Fraction A qualitatively exhibited a trend toward reduced iNOS protein expression compared with n-butanol and aqueous fractions. Exploratory microarray and pathway analyses suggested a possible association with NF-κB and TNF-related pathways. LC-HRMS and molecular docking indicated that emodin-8-O-β-D-glucopyranoside, one of the tentatively annotated compounds in Fraction A, may interact with IL-1β at site A. These findings provide preliminary, exploratory, and hypothesis-generating insights into of the anti-inflammatory and potential hepatoprotective activity of Fraction A. GRAPHICAL ABSTRACT